The first species of Eutheia (Coleoptera, Staphylinidae, Scydmaeninae) in Pakistan - Jałoszyński, Paweł (Zootaxa, 2018)
Eutheia Stephens, 1830 is distributed in Holarctic and Neotropical regions, with a majority of species known to occur in the Palaearctic. Recent studies focused on the Russian Far East, China, Taiwan and Japan yielded many new species (Hoshina 2007; Jałoszyński 2004, 2008a, 2008b, 2010a, 2010b, 2013; Kurbatov 1990, 1991). Central and South Asia are very poorly studied, as these areas include several countries whose geopolitical situation makes field studies difficult. Besides two Himalayan species of Eutheia discovered in Nepal (Franz 1974, 1985), the scydmaenine fauna of the vast area comprising Afghanistan, Pakistan and some of the former Soviet republics is very poorly known. Southern areas of this region (mostly India) are better studied, but as Eutheia prefers temperate climate and even in the Neotropics and in Taiwan can be found only in high mountains (Jałoszyński 2008b, 2011), it is not very likely to find this genus far south of the mountain arc formed by the Himalayas, Karakoram and Hindu Kush. Pakistan, with its potentially species-rich, forested sub-Himalayan region with a subtropical highland climate, is exceptionally poorly studied, with only four species of Scydmaeninae recorded: Scydmoraphes gartneri (Franz, 1979), Scydmoraphes hastipes Vít, 1999, Stenichnus fallax Vít, 1999 (all Glandulariini), Scydmaenus minangkabauensis C. Blattný, 1926 and Scydmaenus ravalpindii Franz, 1970 (Scydmaenini). However, some of these species remain problematic. The identity of Pakistani material of Sc. minangkabauensis remains unclear, as this species was described from Sumatra, and recorded from Vietnam, southern China, Java, Sri Lanka, Nepal and Pakistan (e.g., Franz 1982). Such a broad distribution seems unlikely, especially that many species of Scydmaenus share very uniform appearance and their aedeagi were often studied and illustrated by Franz just in any possible view, depending on how they solidified in euparal, without making any attempt to obtain repeatable preparations. Stenichnus fallax, in turn, is very likely a junior synonym of Stenichnus rothangensis (Franz, 1981), a species redescribed by Jałoszyński (2015) and known to occur in the Indian state of Himachal Pradesh, not far from the type locality of St. fallax.